Travelling Chronicles News and Newspapers from the Early Modern Period to the Eighteenth Century - Gøril Brandtzæg, Siv; Goring , Paul; Watson , Christine (Library of the Written Word - The Handpress World, 2018)
Travelling Chronicles presents fourteen episodes in the history of news and newspapers, from the early modern period to the eighteenth century, written by some of the leading scholars in the rapidly developing fields of news studies.